A comparative evaluation of changes in facial parameters in partial secondary adentia - Ibragimova F.I.; Qurbonov D.F (International Journal on Human-Computing Studies, 2021)
Anthropometric methods are methods in which on the basis of which the continuity of the three sections of the face lies the pirincipus. They were invited by the circus" Golden Section " A. The method of quot; Yupis; gave the confirmation that the distance between the angle of the eye and the angle of the mouth is equal to the distance between the tip of the nose and the chin in the case of Central occlusion F. Quot; Vutsvord method; determined the height of the lower part of the face by the expression of the nasal-lab layers A. Gizi method. These techniques are mainly used in prosthetics in different manifestations of adentia. In partial secondary adentia, it is impossible not to use anthropometric measurements